Exploring Evidence-Based Analysis of The Plight of Awaiting Trial Inmates in North-Central Nigeria - Salawu, Ibrahim O (Jejaring Administrasi Publik, 2024)
Inmates awaiting trial are individuals who have not yet received a legal conviction for any crime, yet they remain in police or correctional custody. This study assessed the increasing number of awaiting trial inmates across correctional facilities in North Central Nigeria with evidence from Kwara State. The study obtained primary data through semi-structured interviews, key informant interviews (KII), and focused group discussions (FGD). The panel data from the Nigerian Correctional Service (NCS) and other secondary sources to complemented the information. Structural functionalism was the theoretical framework for the study. The population for the study consists of inmates awaiting trial, top officials of the Nigerian Correctional Service (NCS), senior police officers with prosecutorial experience, and lawyers and magistrates with cognate experience in litigation. The study revealed that the increase in awaiting trial inmates is largely responsible for recorded jailbreaks in the region. It also revealed that prison congestion and the overstretch of physical infrastructure available for convicted inmates results from legal technicalities that make it difficult for bail conditions to be easily met and the nature of crimes committed. The study recommended constitutional reviews to make the surety system less burdensome. This will go a long way toward easing and speeding up the justice delivery system. Budgetary allocations to the statutory bodies in the justice delivery system should be increased to increase the holding capacity of the correctional facilities, the courts and modern court infrastructure, and police stations. Keywords: Inmates, Awaiting Trial, Correctional Service, Convict, Structural Functionalism